Hysteroscopy in patients with infertility - Vergara, Carlos (2015)
We performed hysteroscopic evaluation to 286 patients with either primary (n=205, 71,6%) or secondary (n=81; 28,3%) infertility. Stenosis (6,2%), polyps (4,1%), and internal orifice insufficiency (1,7%) were found in the uterine cervix; and hyperpalsia (26,9%), sinequiae (24,1%), polyps (20,2%), myomata (11,8%), endometritis (6,2%), hypoplasia (1,3%) and malformations (1,0%) at the uterine corpus. Abnormalities in one of every three patients would have not been diagnosed without hysteroscopic study.